2015
DOI: 10.1242/dmm.022020
|View full text |Cite
|
Sign up to set email alerts
|

A modified choline-deficient, ethionine-supplemented diet reduces morbidity and retains a liver progenitor cell response

Abstract: The choline-deficient, ethionine-supplemented (CDE) dietary model induces chronic liver damage, and stimulates liver progenitor cell (LPC)-mediated repair. Long-term CDE administration leads to hepatocellular carcinoma in rodents and lineage-tracing studies show that LPCs differentiate into functional hepatocytes in this model. The CDE diet was first modified for mice by our laboratory by separately administering choline-deficient chow and ethionine in the drinking water (CD+E diet). Although this CD+E diet is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…In parallel, if they are too young or too little (<15 g) at the time of dietary exposure, toxicity and ensuing mortality might be excessively high. With the administration of the CDE diet to mice of 6 weeks of age and with a body weight between 18 and 20 g, we and others show a substantial and reasonably reproducible LPC response while maintaining the well-being of the animals [24,28,29,35]. Mice are experiencing the most severe effects of the diet during the first week of administration.…”
Section: Mouse Variablessupporting
confidence: 53%
See 4 more Smart Citations
“…In parallel, if they are too young or too little (<15 g) at the time of dietary exposure, toxicity and ensuing mortality might be excessively high. With the administration of the CDE diet to mice of 6 weeks of age and with a body weight between 18 and 20 g, we and others show a substantial and reasonably reproducible LPC response while maintaining the well-being of the animals [24,28,29,35]. Mice are experiencing the most severe effects of the diet during the first week of administration.…”
Section: Mouse Variablessupporting
confidence: 53%
“…This makes it difficult to control effective ethionine intake. Addition of 5% sucrose, choline-free orange juice, or fruit syrup is sometimes used to increase the attractiveness of the drink and this is most of the time not reported in the experimental protocol [9,23,28,29,[32][33][34]. Ethionine smell increases with exposure to the ambient air and we found that we could maintain stable water intake by replacing ethionine-containing water by a fresh solution every day.…”
Section: Experimental Animal Models Of Human Diseases -An Effective Tmentioning
confidence: 78%
See 3 more Smart Citations